Comparison of single and multi-user pre-filtering techniques using different chip mapping for DL MC-CDMA systems - Silva, Adão
In this paper we compare the performance of the joint space-frequency single and multi-user pre-filtering techniques that have been proposed recently for DL MC-CDMA systems. We consider the use of antenna arrays at the base station and a single antenna at the mobile terminal (MT). We investigate how the chip mapping strategy impacts on the performance of the pre-filtering approaches. Thus, practical combinations of prefiltering and chip mapping are discussed. The performance is evaluated for different chip mapping strategies, considering typical indoor and pedestrian scenarios and both uncoded data and channel turbo coding based on UMTS specifications. © 2007 IEEE.